PENGGUNAAN ALAT PERMAINAN EDUKATIF (APE) PADA TAMAN KANAK-KANAK SE-KOTA METRO - Uswatun Hasanah (AWLADY : Jurnal Pendidikan Anak, 2019)
Educators in managing the use of educational games should be able to develop patterns of interaction between various parties involved in learning and must be good at motivating students to be open, creative, responsive, and interactive in learning activities.Based on the background above, researchers want to find out: 1) The types of Educational Game Tools (APE) are used in kindergarten in Metro. 2) Managing the use of Educational Game Tools (APE) in kindergartens in Metro. 3) Accuracy in the use of Educational Game Tools (APE) in kindergartens in Metro.The method of this research is a qualitative naturalistic research method. The respondents from this study were: RA Perwanida, TK of the Pembina Negeri Metro City, TK Pertiwi.The results of this study are: 1) Types of Educational Game Tools (APE) in Kidergarten in Metro, namely: The use of Educational Game Tools used in Kindergarten in Metro, the researcher divided them into two types, namely: a ) Indoor educational tools (APE) include: Lego, circle towers, geometry towers, origami, rubber balls, story books, and congklak. b) Outdoor Educational Games Tools (APE), including: Slide, Seesaw, Swing, Rocking Bridge, World Ball, Swivel Train, Swing Train; 2) The management of using APE at Kindergarten in Metro City adjusted to RPPH (Daily Learning Implementation Plan); 3) The accuracy of the use of APE in TK throughout the Metro City can be obtained by prioritizing the selection of APE in terms of its usefulness which impacts on aspects of child development.